2017
DOI: 10.1002/prot.25433
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of nucleotide‐binding domain dimerization in the intact maltose transporter as studied by all‐atom molecular dynamics simulations

Abstract: The Escherichia coli maltose transporter MalFGK -E belongs to the protein superfamily of ATP-binding cassette (ABC) transporters. This protein is composed of heterodimeric transmembrane domains (TMDs) MalF and MalG, and the homodimeric nucleotide-binding domains (NBDs) MalK . In addition to the TMDs and NBDs, the periplasmic maltose binding protein MalE captures maltose and shuttle it to the transporter. In this study, we performed all-atom molecular dynamics (MD) simulations on the maltose transporter and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…These results strongly support the idea that maltose-bound MalE stimulates the ATPase activity of the transporter by promoting MalK closure [99]. This was later corroborated by the EPR work of Bordignon’s team [86] and more recently by molecular dynamic simulations [100]. Similarly, using spin-labeled MalE [45], other studies showed that ATP binding leads to the opening of MalE [68], [95].…”
Section: Step 3 and 4: Substrate Delivery And Import Mechanismsupporting
confidence: 66%
“…These results strongly support the idea that maltose-bound MalE stimulates the ATPase activity of the transporter by promoting MalK closure [99]. This was later corroborated by the EPR work of Bordignon’s team [86] and more recently by molecular dynamic simulations [100]. Similarly, using spin-labeled MalE [45], other studies showed that ATP binding leads to the opening of MalE [68], [95].…”
Section: Step 3 and 4: Substrate Delivery And Import Mechanismsupporting
confidence: 66%
“…The analysis of the free energy landscapes for the opening-closing of the maltose transporter ATPase MaIK(2) has been conducted using enhanced-sampling molecular dynamics . In contrast, an all-atom molecular dynamics simulation dealt with the mechanism of nucleotide-binding domain dimerization in the intact Maltose Transporter …”
Section: Protein Carbohydrate Interactionsmentioning
confidence: 99%
“…On the other hand, in the absence of MalE, the transmembrane helices of MalF arrange in a way that blocks the translocation pathway. MalE binding also suppresses fluctuation of the P2-loop of MalF 15 . The effect of nucleotide binding to the NBDs was also simulated, as well as its energetic and mechanistic charcterization 15 18 .…”
Section: Introductionmentioning
confidence: 98%
“…MalE binding also suppresses fluctuation of the P2-loop of MalF 15 . The effect of nucleotide binding to the NBDs was also simulated, as well as its energetic and mechanistic charcterization 15 18 . ATP binding in both pockets induces the closed form of the NBD dimer, while ATP hydrolysis triggers dimer opening 16 .…”
Section: Introductionmentioning
confidence: 98%